Making Vector-Borne Disease Surveillance Work: New Opportunities From the SDG Perspectives - Braks, Marieta; Giglio, Giorgia; Tomassone, Laura; Sprong, Hein; Leslie, Teresa (Frontiers in Veterinary Science, 2019)
Surveillance of vector-borne diseases (VBDs) exemplifies a One Health approach, which entails coordinated, collaborative, multidisciplinary and cross-sectoral approaches to address potential or existing health risks originating at the animal-human-ecosystem interface. However, at the intervention stage of the surveillance system, it is sometimes difficult or even impossible to act. The human dimension of VBD control makes them wicked problems requiring an interdisciplinary systems approach beyond the One Health domain. Here, we make a case that the agenda of the UN Sustainable Development Goals (SDGs) can offer new opportunities to address these issues. The health of the population is a concern to us all and is more or less related to all 17 SDGs. The SDGs can provide a common language by which the interests of various stakeholders can be matched and the challenges that society faces identified, studied and alleviated. To illustrate, the control and prevention of two VBDs, dengue and Lyme borreliosis, were selected and related to specific SDGs. Further, we use the framework proposed by the International Council of Science to: (1) show synergies and trade-offs between the various SDGs; and (2) present SDG 3 to identify policy that can be related to prevention. Engaging in an integrated approach will confront stakeholders with various viewpoints and through these oppositions, innovation can be nurtured. By adhering to the SDG agenda, we present policy advice including new opportunities for vector-borne disease control to reach its own health goals, while simultaneously supporting other sustainable development goals.